A modular and scalable system for electromagnetic compatibility testing of integrated circuits - Kircher, Daniel; Profanter, Simon; Deutschmann, Bernd (Elektrotechnik und Informationstechnik, 2024)
To bring automotive integrated circuits (ICs) to market, manufacturers must subject their products to numerous electromagnetic compatibility (EMC) tests such as electromagnetic immunity and emission tests, or electrostatic discharge (ESD) tests. These tests need EMC test boards that meet the requirements of the specific standards. However, the current need to increase the frequency range of EMC tests poses a challenge in designing standard-compliant test boards. In this paper, we address this issue by introducing a modular and reusable IC level EMC test system. We demonstrate the system’s effectiveness with an example of two frequently used and conducted EMC tests: the direct power injection (DPI) immunity test and the 150 Ω electromagnetic emission measurement. The two test setups are constructed and validated using the presented modules. It is shown how the frequency range can be expanded while minimizing costs and design efforts for the EMC test board design.